1998
DOI: 10.1007/bf02495526
|View full text |Cite
|
Sign up to set email alerts
|

Ajanolide A, a new germacranolide fromAjania fruticulosa

Abstract: A new germacranolide, ajanolide A, was isolated from aerial parts of Ajania fruticulosa by means of extraction with CHCI 3 and adsorption chromatography. This compound was identified as (l(lO)E,3S,4Z,6R,7S,11R)-3-acetoxygermacra-l(lO),4~ (( I S,7S, 1 OR, 13 R)-%acetoxy-4,8,13-trimethyl-11 -oxabicycIo[8.3.0]trideca-4(E),8(~-dien -12-one) by X-ray diffraction analysis. 2D IH--tH (COSY) and t3C--1H (COSY) NMR spectroscopy was used for assigning the tH and 13C NMR signals in the spectra of ajanolide A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The coupling constants across the protons at positions H-5-H-7 (J 5,6 =11.0 Hz and J 6,7 was very small and not measurable) were equivalent to the literature values for heliangolides such as provincialin, heliangolidin, and ajanolide A. [21][22][23] Further relative stereochemistry of 2 was confirmed by NOESY experiment. The NOE correlations (Fig.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The coupling constants across the protons at positions H-5-H-7 (J 5,6 =11.0 Hz and J 6,7 was very small and not measurable) were equivalent to the literature values for heliangolides such as provincialin, heliangolidin, and ajanolide A. [21][22][23] Further relative stereochemistry of 2 was confirmed by NOESY experiment. The NOE correlations (Fig.…”
Section: Resultssupporting
confidence: 79%
“…The Z-configuration of the Δ 4 -double bond and the E-configuration of the Δ 1(10) -double bond were confirmed by NOE correlations between H-5 and H-15 and between H-6 and H-14, respectively. Therefore, compound 2 was identified as 3β-acetoxy-15-hydroxy-germacra-1(10)E,4Z-dien-6β,7α,11αH-12,6-olide (15-hydroxyajanolide A) 23) and named zawadskinolide B.…”
Section: Resultsmentioning
confidence: 99%
“…The plant has been used to treat appendicitis, tuberculosis, and emphysema in Chinese folk medicine . The literatures have shown that the main secondary metabolism of the plant included sesquiterpenes, flavonoids, sesquiterpene lactone, and phenolics . In this paper, we investigated the insecticidal activities of the essential oil, and the compounds from A .…”
Section: Introductionmentioning
confidence: 99%